Magnetic properties and electronic structure of LaFeAsO0.85F0.1 - Fedorchenko, A.V.; Grechnev, G.E.; Desnenko, V.A.; Panfilov, A.S.; Volkova, O.S.; Vasiliev, A.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
The magnetic properties of LaFeAsO0.85F0.1 compound were investigated by measurements of dc magnetization at different values of the magnetic field, H = 0.02, 1.0 and 2.0 T, in the temperature range 4.2–300 K. The superconducting behavior was found below 26 K, whereas a distinct peculiarity in the low-field dependence of the magnetic susceptibility c(T) was clearly observed at TM≃ 135 K, which resembles a weak ferromagnetic (FM) response with saturation magnetic moment of about 10–4 μB per formula unit at 50 K. The transition at TM is presumably not governed by magnetic impurities but rather correlated with the antiferromagnetic (AFM) transition in the undoped LaFeAsO compound at about the same temperature. We suggest, that observed magnetic properties of the LaFeAsO0.85F0.1 sample are due to an interplay of FM and AFM transitions, and presumably related to an intrinsic feature of a small portion of the undoped LaFeAsO phase inherent in our sample. In order to shed light on the problem of magnetic instability of the LaFeAsO, the ab initio DFT calculations of electronic structure and paramagnetic susceptibility were performed within the local spin density approximation. It is shown, that a V-shaped peculiarity in the density of electronic states in a close vicinity of the Fermi level can govern magnetic properties of LaFeAsO under fluorine doping and/or oxygen deficiency.